A series of emergency presentations of diverticular disease of colon - Sabu M., Ravi Kumar; R., Kannan; Prabakar, Joyce (International Surgery Journal, 2022)
Diverticular disease of the colon is commonly prevalent in developed countries, especially in the western population. This is mainly attributed towards their food habits which include less dietary fibre which is the primordial cause of diverticular disease. Its incidence is gradually increasing in developing countries, especially in southern parts of India due to rapid change in food habits which are moving towards western culture. Majority of the patients with diverticular disease may remain asymptomatic. Diverticular disease presents to the hospital with a wide variety of symptoms such as lower abdominal pain, fever, malaise, bleeding per rectum which manifests because of its complications. Hence the early presentations of diverticular disease should not be missed and proper evaluation should be carried out in suspicious cases to prevent complications which can be deadly. Here we present a series of cases that are received in our emergency department as a complication of diverticular disease. This is a case series in which we study the emergency presentations of diverticular diseases admitted in Rajiv Gandhi government general hospital. Here diverticular disease is proven by a series of investigations that include evaluation of acute abdomen such as x ray abdomen erect, ultrasound abdomen, contrast enhanced computed tomography and histopathological examination with appropriate management.